2012
DOI: 10.1038/ki.2012.241
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ischemic preconditioning contributes to renal protection by upregulation of miR-21

Abstract: Delayed ischemic preconditioning effectively protects kidneys from ischemia-reperfusion injury but the mechanism underlying renal protection remains poorly understood. Here we examined the in vivo role of microRNA miR-21 in the renal protection conferred by delayed ischemic preconditioning in mice. A 15 minute renal ischemic preconditioning significantly increased the expression of miR-21 by 4 hours and substantially attenuated ischemia-reperfusion injury induced 4 days later. A locked nucleic acid-modified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
191
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(201 citation statements)
references
References 53 publications
6
191
1
Order By: Relevance
“…On the other hand, knockdown of miR-21 resulted in signifi cant up-regulation of PCDP4 and a substantial increase in tubular cell apoptosis. The same study also showed that miR-21 performed a renal protective effect by further delaying IPC against subsequent renal IRI (Xu et al 2012) . Therefore, up-regulation of miR-21 during a short period of ischemia followed by reperfusion can activate endogenous defense mechanisms that protect against a subsequent, sustained ischemic insult; however, imbalanced expression may contribute to a serious irreversible outcome.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the other hand, knockdown of miR-21 resulted in signifi cant up-regulation of PCDP4 and a substantial increase in tubular cell apoptosis. The same study also showed that miR-21 performed a renal protective effect by further delaying IPC against subsequent renal IRI (Xu et al 2012) . Therefore, up-regulation of miR-21 during a short period of ischemia followed by reperfusion can activate endogenous defense mechanisms that protect against a subsequent, sustained ischemic insult; however, imbalanced expression may contribute to a serious irreversible outcome.…”
Section: Discussionmentioning
confidence: 52%
“…MiR-21 has been reported to promote such proliferation and act as a strong anti-apoptotic factor to inhibit cell death (Chan et al, 2005;Cheng et al, 2010;Godwin et al, 2010). Recent fi ndings have also shown that up-regulation of miR-21 contributed to a reduction in renal cell apoptosis and it also consistently shows protective effects against renal IRI after ischemic preconditioning (IPC) (Xu et al, 2012).…”
Section: Protein Cellmentioning
confidence: 91%
“…This is in contrast to a previous study in which a 15-minute IPC regimen attenuated IRI induced 4 days later, associated with up-regulated miR-21 and hypoxiainducible factor 1α expression. 16 Similar to our study, this previous study used an IPC regimen of 15 minutes of continuous ischemia, but the extended period of 4 days between IPC and IRI may be key in terms of understanding the different outcomes. A beneficial effect after this extended recovery may support improvements in tissue robustness to subsequent injury that take hours rather than minutes to set in place.…”
Section: Discussionmentioning
confidence: 68%
“…15 Another study identified the importance of miR-21 in a mouse model of IRI and IPC. 16 In that study, 15 minutes of localized IPC significantly increased miR-21 expression, resulting in attenuation of IRI 4 days later, whereas knockdown of miR-21 significantly increased tubular cell apoptosis. 16 The purpose of this study was to determine whether a 15-minute localized IPC regimen attenuated injury in a rat model of unilateral IRI.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation